Exploration of Aedes breeding site with the evidence of different types of container in plant nursery, Klang, Malaysia / Intan Syanurin Jifri ... [et al.] - Jifri, Intan Syanurin; Mohd Yatim, Siti Rohana; Selamat, Neni Widiasmoro; Shari, Norshafarina; Zaki, Muhammad Afiq (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Dengue fever which transmitted by the Aedes mosquitoes has been one of the most widespread vector-borne disease. The most important thing in reducing the dengue infection cases is by controlling the populations of the Aedes mosquito by destructing Aedes breeding sites. Aedes breeding sites was determined by conducting a larval survey. Most of the study that has been conducted are targeting the housing area since it is a resident of human. However, plant nursery can be one of the contributors for the increasing of dengue especially the one located near the housing area. This is because the potential container such as flowerpot plate, tires and bucket also could be found in plant nursery. This study helps to identify any natural or artificial breeding site that can be found in a plant nursery and if this potential breeding site can give impact to the Aedes population. Container survey were used to identify the potential breeding site at the plant nursery and larvae collection was conducted to depicting positive breeding site. Overall, 68 containers were found as potential breeding sites hence artificial container was found to be the main contributor to the increasing of positive breeding site in plant nursery. Henceforth, the relationship between the type of container and positive breeding site was determined by their likelihood to breed in the container with large surface area such as bucket and shaded area such as tires and bucket.